Alternate wetting and moderate soil drying (AWMD) enhances the physicochemical properties of rice starch by promoting grain-filling in inferior grains of rice - Tianyang Zhou; Chengcheng Ge; Yuguang Zang; Kuanyu Zhu; Weiyang Zhang; Hao Zhang; Lijun Liu; Zhiqin Wang; Junfei Gu; Jianchang Yang (Food Chemistry: X)
Water scarcity is the major challenge to sustainable rice production. This study examines how alternate wetting and moderate soil drying (AWMD), a widely adopted water-saving practice, influences grain-filling dynamics and starch physicochemical properties in both superior grains (located on apical primary branches, flower earlier) and inferior ones (located on proximal secondary branches, flower later). Results showed that AWMD enhanced grain-filling in inferior grains: it increased the mean (Gmean) and peak (Gmax) filling rates by 26.9 % and 26.3 % respectively, while shortening the filling duration (D) by 14.1 %. These changes ultimately enhanced carbohydrate supply and starch accumulation. Biochemically, AWMD promoted a short-chain amylopectin structure, increasing amorphous polymer content, short-range disordered molecular arrangements, and reducing relative crystallinity. These structural modifications enhanced starch pyrolysis rates, viscosity, breakdown, and adhesiveness, while decreasing phase transition temperature, gelatinization enthalpy, and hardness. The study demonstrates that AWMD not only reduces irrigation demand but also improves starch quality, especially in low-quality inferior grains, through optimized grain-filling kinetics. These findings suggests that AWMD is an effective strategy for the sustainable production of high-quality rice starch for food use.